2004
DOI: 10.1021/ic0301167
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Magnetic g Tensors and the Local Cysteine Geometries for a Series of Reduced [2Fe−2S*] Protein Clusters. A Quantum Chemical Density Functional Theory and Structural Analysis

Abstract: We relied on the density functional theory (DFT) to study the electronic structure of the [2Fe-2S*](SH)4 model of the active site of 2Fe ferredoxins and other proteins containing reduced [2Fe-2S*] clusters. The two (Fe(3+)-Fe(2+)-S-H) dihedral angles Omega1 and Omega2 defined for the two ligands on the ferrous side were allowed to vary, while the two other (Fe(2+)-Fe(3+)-S-H) angles Omega3 and Omega4 on the ferric side were kept constant. The Landé (g), magnetic hyperfine, and quadrupole tensors for two geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 75 publications
3
20
0
Order By: Relevance
“…Changes in the rhombicity of the EPR signal of [2Fe-2S] clusters have been attributed to a change in the angle between the iron/iron plane of the cluster and the plane between the sulfur ligand and its adjacent carbon atom [37], therefore implying a structural rearrangement of the cluster environment. Some of the several available 3D structures of complexes II resolve the position of water molecules and show several of them at the interface between subunits A and B close to the flavin and the [2Fe-2S] cluster, connecting the two cofactors via a hydrogen bond network.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the rhombicity of the EPR signal of [2Fe-2S] clusters have been attributed to a change in the angle between the iron/iron plane of the cluster and the plane between the sulfur ligand and its adjacent carbon atom [37], therefore implying a structural rearrangement of the cluster environment. Some of the several available 3D structures of complexes II resolve the position of water molecules and show several of them at the interface between subunits A and B close to the flavin and the [2Fe-2S] cluster, connecting the two cofactors via a hydrogen bond network.…”
Section: Resultsmentioning
confidence: 99%
“…Orientation of the g -tensor principal directions for the reduced [2Fe-2S] cluster in adx and fdx was previously determined from the simulation of the orientation selected proton ENDOR spectra 26,27. According to these studies, the g-tensor principal axes are displaced from those theoretically predicted39,40 as exactly along the S-S, Fe-Fe, and nearly normal to the cluster plane directions. For instance, the g 1 direction in adx is about 24º, with the normal of the averaged plane spanned by the FeSSFe core.…”
Section: Discussionmentioning
confidence: 99%
“…As for the mixture of five d-orbitals occupied by ctelectrons, the mixing has no influence on the resulting Slater determinant. Note that in quantum chemical calculations, utilizing unrestricted self-consistent field theory (USCF) or unrestricted density functional theory (UDFT), 3d-orbitals for c~-and [3-electrons may be significantly different and split (by about 5 eV), because of the internal exchange polarization, which is typical for unrestricted methods [13,14]. In this case, the single determinant wave function for Fe 2 § is usually contaminated by the admixture of high-spin (S 2 > 2) components.…”
Section: Theoreticai Backgroundmentioning
confidence: 99%
“…Nevertheless, the possible importance of SR group orientation for tuning of catalytic and electron-transfer function of different ferredoxin proteins was also mentioned. These analyses were recently extended by Gambarelli and Mouesca [14] using a DFT approach to two other (C 2 and Cs) geometries of [2Fe-2S*](SH)4 cluster. Analysis of the available Xray structures of the proteins with such clusters performed in reŸ 14 showed that the major difference between them is in the coordination geometry of the cysteine ligands.…”
Section: G-tensor Calculationsmentioning
confidence: 99%